ANALYSIS OF EDUCATIONAL MODELS IN THE CONTEXT OF FORMING LIFE SUCCESS RATE OF SENIOR CLASS STUDENTS - Yezhova, Olha (Theoretical and Methodical Problems of Children and Youth Education, 2023)
The article analyzes the educational models of foreign scientists to determine the conditions and indicators of the future model of the process of forming the life success rate of high school students. We consider this stage mandatory at the beginning of the study of the complex and multidimensional psychological and pedagogical process of forming the life success of senior class students in the conditions of the post-war reality. The development of one's own model of this process requires the study of such existing educational models, the result of which is related to success. To achieve the goal, scientific sources were studied according to the Scopus and Web of Science scientometric databases. Theoretical methods of analysis, synthesis, abstraction, generalization, concretization, and systematization were used to study models of the educational process and identify their characteristic features. The following models were chosen to develop a model for the formation of the success rate of high school students in post-war reality: The Positive School Climate Model, the Personalized Learning Model, the Growth Mindset Model, The Social Support Model, the Collaboration Model. For each selected model, we identified leading components and determined indicators studied by foreign scientists. The analysis of studies of models of educational processes by foreign scientists allowed us to conclude that the majority connects the leading components and characteristics of the models with the academic success of students. For the model of formation of life success of high school students, important conditions should be: provision of a favorable educational environment; ensuring constructive interaction in the student body; social support of students; development of partnership and cooperation during training. Several life skills have been singled out for student success: assertiveness, empathy, decision-making, leadership, ability to work in a team, perseverance and resilience in overcoming obstacles – with which scientists associate student success rate, and which can potentially be indicators of the effectiveness of our future model.